RELIGION IN GLOBAL POLITICS: EXPLAINING DEPRIVATIZATION - Haynes, Jeff (Jurnal Ilmiah Peuradeun, 2015)
Examples of religion’s recent political impact abound in states at varying levels of economic and political development. The paper examines the relationship between religion and politics over the last quarter century in a variety of countries; in effect, a global survey. What was new and became ‘news’ in the 1980s was the widespread and simultaneous refusal of the so-called ‘world religions’ - Islam, Christianity, Hinduism and Buddhism - to restrict them selves to the private sphere. Religious organizations of various kinds seem openly to be rejecting the secular ideals dominating most national policies, appearing as champions of alternative, confessional options. In keeping faith with what they interpret as divine decree, increasingly they refuse to render to nonreligious power either material or moral tribute. They are also refusing to restrict themselves to the pastoral care of individual souls, instead raising questions about, inter alia, the interconnections of private and public morality and the claims of states and markets to be exempt from extrinsic normative considerations.